Illegal Access dalam Aktivitas Tambang Inkonvensional di Desa Baturusa Kabupaten Bangka - Ego Saputra, Muhammad (Jurnal Studi Inovasi, 2024)
This research discusses illegal access to unconventional mining activities in Baturusa Village, Bangka Regency. Baturusa Village is a region characterized by its vast reserves of tin. Consequently, this has resulted in the proliferation of illegal tin mining operations. This leads to environmental issue, specifically the shallowing of rivers caused by sedimentation resulting from illegal tin mining and the creation of kolong after mining. Furthermore, the community’s reliance on tin resources to meet their economic needs has lad to an increase in illegal tin mining operation in Baturusa Village, causing significant environmental degradation, particularly in river ecosystems. Moreover, an established network facilitates illegal tin mining activities by providing miners with convenient access to engage in their operation. It means that actor networks are an inherent component of exploitative and extractive economic actions. Additionally, miners possess an access mechanism that facilitates the acquisition, maintenance, and preservation of resource access mechanism through processes, facilities, and tools. Apart from that, miners have an access mechanism that simplifies the acquisition, upkeep, and maintenance of resources. This mechanism encompasses many processes, facilities, and relationships involved in conducting tin mining activities. In the case, illegal tin mining activities in Baturusa Village are very difficult to control or stop. The objective of this study is to examine the access network and method used in unconventional mining operations in Baturusa Village, Merawang District, Bangka Regency. The research utilizes the theory of Access developed by Jesse Ribot and Nancy Lee Peluso. The research used a qualitative methodology. This research employed interviews, observation, and documentation for data collection. Keywords: Illegal Mining, Illegal Access, Access Network